Pengaruh Keselamatan, Kesehatan Kerja (K3) dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Pada Bagian Instalasi Produksi Pabrik Gula Tjoekir Jombang - Rofina Innunisa (BIMA : Journal of Business and Innovation Management, 2019)
This study aims to determine the effect of Occupational Safety, Health (K3) and Work Discipline on Employee Productivity. The population in this study were all production plant employees, amounting to 93 respondents. Data analysis techniques used in this study used multiple regression analysis with a level of sig <0.05. Based on the t test results the Occupational Health and Safety variable has a significance value of 0,000 <0.05 so it can be said that the K3 variable has a partially positive and significant effect on employee productivity. Based on the t test results the Work Discipline variable gets a significant value of 0,000 less than 0.005, it can be said that the work discipline variable partially has a significant positive effect on employee work productivity. Based on the results of the f test variables of safety, occupational health and work discipline get a significance value of 0,000 less than 0.05.